PENTINGNYA PELAYANAN BIMBINGAN DAN KONSELING BAGI PESERTA DIDIK PADA TINGKAT SEKOLAH MENENGAH ATAS (SMA) - Seme Ea, Selvira; Yuvani, Maria (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2023)
Character education is one focus and orientation in the education world system. Therefore, educators should not be apathetic or indifferent to this. School counselors, as individuals whose role is to educate and teach good character to students, must be more responsible for these good goals. Thus, a noble goal can be implemented by students in their reel life in the context of culture and society. The important role of a school counselor lies not only in giving suggestions and suggestions, but also in educating students with full patience and full responsibility for the problems experienced by these students. On an individual basis, school counselors can provide services, such as individual services, individual planning services, and responsive services. Character education is one of the educational movements in schools to strengthen student character through harmonization of heart (ethics) and thought (literacy). Meanwhile, guidance and counseling services are one of the service programs that are fair in implementing programs in schools. Thus it is hoped that the implementation of strengthening character education through guidance and counseling services will be easy to carry out effectively and efficiently, in order to achieve the goal of starting and optimizing the development of character values ​​that exist in students.